Fetal Biometry in the Third Trimester; Local Perspective (Medical Forum Monthly, 2024)
Objective: To observe the frequently used parameters of fetal biometry along with ultrasonographic appearance and measurement of epiphyseal ossification centres of fetal peripheral long bones in our local population for assessment of gestation age in the third trimester.Study Design: Descriptive, Observational studyPlace and Duration of Study: This study was carried out at Department of Radiology, Dow University of Health Sciences/Civil Hospital Karachi from February 2009 to July 2009.Materials and Methods: 200 pregnant females were examined having gestational age of 28 or more weeks. Obstetrical ultrasound was done using 3.5MHz convex transducer on Toshiba ultrasound scanner model Nemio-17. Measurement of Biparietal Diameter, (BPD), femur Length (FL) and abdominal Circumference (AC), placental localization and assessment of liquor was done as per standard protocol. The distal femoral, proximal tibial and proximal humeral ossification centers were identified and measured.Results: The frequently used parameters of fetal biometry along with ultrasonographic appearance and measurement of epiphyseal ossification centres of fetal peripheral long bones for assessment of gestation age in the third trimester in our local population are in agreement with international studies.Conclusion: Ultrasonographic visualization of the epiphyses ossification centers in correlation with fetal biometry is a useful marker of fetal gestational age in third trimester.